2014
DOI: 10.4172/1948-5956.1000311
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Nitric Oxide and TNF-Α in Newcastle Disease Virus (NDV) AF2240 Infected RAW 264.7 Macrophages and their Cytotoxic Activity on MDA-MB-231 Breast Cancer Cell Line

Abstract: Background: It is well known that Newcastle Disease Virus (NDV) AF2240 has antitumor activity against breast cancer cell lines. Several studies have thought this activity depend on direct viral oncolysis, which may not be the only factor that play a role in the antitumor effect of the virus. However, the mechanism underlying its antitumor effect is largely unresolved. In line with this observation, we postulated that NDV AF2240 may induce an in vitro production of Nitric Oxide (NO) and Tumor Necrosis Factor (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Due to its unique mechanism of action and its ability to impact on many types of human cancer, NDV has been proposed as a potent anti-cancer agent. Many strains of NDV were found to exhibit anti-cancer activity, for instance, MTH-68/H and AF2240 exhibited its anti-tumour effect via induction of nitric oxide synthesis from macrophages [40, 41]. In addition, systemic therapy with NDV strain PV701 showed a promising result as an important therapy for patients with a solid tumour [42].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its unique mechanism of action and its ability to impact on many types of human cancer, NDV has been proposed as a potent anti-cancer agent. Many strains of NDV were found to exhibit anti-cancer activity, for instance, MTH-68/H and AF2240 exhibited its anti-tumour effect via induction of nitric oxide synthesis from macrophages [40, 41]. In addition, systemic therapy with NDV strain PV701 showed a promising result as an important therapy for patients with a solid tumour [42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in vitro using the lytic NDV strain 73-T showed that human PBMC upregulate the expression of TNF-α in supernatant after 24 h of stimulation (18,42). Other reports have demonstrated the capability of NDV to stimulate the production of this cytokine, although it was in murine macrophages (19,43). In patients with advanced solid tumors, the administration of a single or multiple doses of the lentogenic NDV PV701 induced the rejection of the tumors with an increased amount in serum of pro-inflammatory cytokines, such as TNF-α (44).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Other studies by Zeng et al and Ahmad et alhave carried out inactivation at UV lamp (245 nm, 2 mW/cm 2 for 30 mins and 15 mins respectively. 14,15 However, our methodology of UV inactivation at 254 nm, power 220µW/cm 2 at distance of 10 cm for 30 mins served the purpose as well as hemagglutinin activity was intact.…”
Section: Discussionmentioning
confidence: 99%